Analysis of slope deformation due to the effect of various rainfall patterns - Asfarina Maidin (2022)
Formation is a geological process that occurred through time. As it related to the movement of the soils, thus instantly it also correlated to the slope stability. There are many formations that existed in Sabah such as Crocker Formation, Trusmadi Formation, Kudat Formation, Garinono Formation, and many more. Therefore, this thesis is focus on the analysis of slope deformation due to the effect of various rainfall patterns at Garinono Formation which more specifically at Location P, Sandakan, Sabah. On top of that, the purpose of this research is to interpret the geotechnical properties of the critical slope, to analysis the change in porewater pressure due to the effect of various rainfall patterns, and to examine the deformation and stability of unsaturated soil due to the effect of varying rainfall patterns. In this research, secondary data which consist of soil investigation report and rainfall tabulation data were obtained from Kumpulan (IKRAM) Sabah Sdn. Bhd. and Jabatan Pengairan dan Saliran (JPS) Sabah respectively. The manipulated variable in this research is the pattern of rainfall which is short-intense (i.e., 2-Hours Rainfall Event) and prolonged (i.e., 48-Hours Rainfall Event). The method of analysis in this research is using Finite Element Method (FEM); numerical simulation conducted using GeoStudio software. Three analyses conducted in this research which consist of transient analysis using SEEP/W, deformation analysis using SIGMA/W, and stability (Factor of Safety) analysis using SLOPE/W. The result shows that, prolonged rainfall presented the significant effects on porewater pressure changes, slope deformation, and factor of safety rather than short-intense rainfall. The porewater pressure change according to the amount of rainfall intensity and the duration of rainfall. Then, both short intense and prolonged rainfall experience large deformation at vertical displacement which deform 1.7 m from the ground surface. In addition, the stability of slope triggered when the rainfall intensity more than saturated hydraulic conductivity values; Layer 1 (i.e., Ksat: 0.2 mm/hr) and Layer 2 (i.e., Ksat: 0.7 mm/hr).